The dirt book : poems about animals that live beneath our feet - Harrison, David L. (David Lee), 1937-; Cosgrove, Kate (New York : Holiday House, 2021)
A collection of poems about dirt and the many organisms that live there such as grubs, trap door spiders, moles, earthworms, chipmunks, and doodlebugs.
This book is about dirt -- Dirt Recipe -- At the Roots of Things -- Doodlebug: One Way Ride -- Trap Door Spider: The Waiting Game -- Earthworm: Dirty Work -- Ant: City Builder -- Grub: Grass Killer -- Mouse: Nightfall Calls -- Bumblebee: Planning for Spring -- Yellow Jacket Wasp: Warning! Warning! Warning! -- Mole: Worm Search -- Toad: Bedtime -- Chipmunk: Busy, Busy, Busy! -- Gopher Tortoise: The Innkeeper -- And Now We Know -- Author notes.
Includes notes about dirt and the organisms that live in it.
School Library Journal, June 2021
Bulletin (Center for Children's Books), May 2021
Kirkus Review, May 2021
Includes bibliographical references.
4.0
Keywords: Soils -- Juvenile poetry; Soil animals -- Juvenile poetry; Children's poetry, American; Soils -- Poetry; Soil animals -- Poetry; Poetry; Nonfiction picture books; Soil animals